Practice of building maintenance management operation processes in office high rise buildings in Malaysia - Mohamad Ridzuan, Yahya (Universiti Malaysia Perlis (UniMAP), 2011)
The 2nd International Conference on the Roles of Humanities and Social Science in Engineering (ICoHSE 2010) organized by Universiti Malaysia Perlis (UniMAP), 12th - 14th November 2010 at Bayview Beach Resort, Penang, Malaysia.